Local Wisdom-Based Education in Bali: Exploring Islamic Values in the Ngejot and Megibung Traditions - Priyatna, Muhamad; Raharjo, Raharjo; Fihris, Fihris; Suretno, Sujian; Mujahid, Ahmad (Pascasarjana UIN ANTASARI Banjarmasin, 2025)
Education is the main foundation in building the character and identity of a nation, especially during the challenges of increasingly rapid globalization. This research aims to explore the integration of Islamic values and local wisdom through the Ngejot and Megibung traditions in Bali, which can enrich the educational curriculum and form a harmonious and tolerant student character. The research method used is a qualitative descriptive study with a literature review approach, which includes the analysis of texts and contexts related to the Ngejot and Megibung traditions and the Islamic values contained in them. This research also emphasizes the role of the community in preserving traditions as part of education based on local wisdom. The results of the study show that education based on local wisdom can improve students' understanding of cultural identity and relevant social values. The Ngejot and Megibung traditions not only function as social practices but also as practical educational tools in instilling the values of solidarity, tolerance, and cooperation. The study also identified challenges in integrating local and Islamic values into the educational curriculum, including a lack of understanding among education managers and the community. Therefore, this study recommends the development of a pedagogical integration model that prioritizes the interaction between Islamic values and Balinese Hindu traditions, as well as strategies to overcome existing challenges. These findings are expected to make a new contribution to the development of education that is inclusive and relevant to the local cultural context, as well as a reference for educators and policymakers in designing curricula rooted in local wisdom and Islamic values.